Two Cases of Spinal Accessory Neuropathy Due to Muscle Injection of Nandrolone For Bodybuilding - Ziba Khanmoradi; Kian Zohrabi; Zohreh Abna (Case Reports in Clinical Practice, 2023)
The accessory nerve is the eleventh cranial nerve that supplies the sternocleidomastoid and trapezius muscles. Injury to the spinal accessory nerve is most commonly caused by medical procedures that involve the head and neck, which causes wasting of the shoulder muscles, winging of the scapula, and weakness of shoulder abduction and external rotation. Here, two cases of spinal accessory neuropathy after injection of trapezius muscle for body building are reported.